Comparison of micro and nano MgO-functionalized vinasse biochar in phosphate removal: Micro-nano particle development, RSM optimization, and potential fertilizer. (February 2021) - Kamali, Nima; Rashidi Mehrabadi, Abdollah; Mirabi, Maryam; Zahed, Mohammad Ali
Graphical abstract: Highlights: Vinasse Biochars were modified with Micro/Nano-MgO at different ratios. Synthesized materials were studied in details by characterization methods. Removal efficiency of the synthesized adsorbent was optimized by RSM. Adsorption isotherms, kinetics, and thermodynamic parameters were investigated. Phosphate loaded modified biochar was proved to be effective in phosphate recovery. Abstract: The present study is conducted to synthesize vinasse-derived biochar, followed by modification with Micro and Nano MgO in an attempt to assess their effects on the phosphate (P) removal from aqueous medium. Based on the characterization results of modified biochars and adsorption capacities, Nano-MgO Functionalized ones have proven to be more capable in P removal, with the specific surface areas of 119.98–125.41 m 2 /g and maximum P adsorption capacity of 188.67 mg/g. The dependencies of adsorption on initial P concentration (50–350 mg/L), contact time (5–90 min), and solution pH level (3–11) were investigated by 20 experiments designed via CCD-based RSM. The regression analysis showed a good fit of the experimental data to the second-order polynomial model with coefficient of determination (R 2 ) value of 0.9916 and model F-value of 131.82. The optimum conditions of pH (7.00), contact time (75 min), and initial P concentration (250 mg/L) were recorded from desirability function. Based on the thermodynamic analysis, the adsorption process was spontaneous and exothermic in nature. In addition, the isotherm and kinetic studies indicated that the Freundlich and the pseudo-second order are the best fitted models for the P adsorption. Further, the P removal efficiency declined slightly in the presence of other co-existed anions, while acted relatively selective towards P. Finally, the P-loaded biochar could be properly regenerated by 1.0 M HCl solution, and the pot experiments proved its applicability as a P fertilizer substitute, increasing the plant growth rate – averagely, the height by 40 % and the dry mass by 59 %.